2015
DOI: 10.1159/000368166
|View full text |Cite
|
Sign up to set email alerts
|

Panel of Urinary Diagnostic Markers for Non-Invasive Detection of Primary and Recurrent Urothelial Urinary Bladder Carcinoma

Abstract: Objectives: To determine the combination of urinary protein markers for noninvasive detection of primary and recurrent urothelial bladder carcinomas. Methods: Urinary concentrations of 27 biomarkers (NSE, ATT, AFABP, Resistin, Midkine, Clusterin, Uromodulin, ZAG2, HSP27, HSP 60, NCAM1/CD56, Angiogenin, Calreticulin, Chromogranin A, CEACAM1, CXCL1, IL13Ra2, Progranulin, VEGFA, CarbAnhydIX, Annexin-V, TIM4, Galectin1, Cystatin B, Synuclein G, ApoA1 and ApoA2) were assessed by enzyme-linked immunosorbent assay or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 27 publications
(29 reference statements)
2
37
2
Order By: Relevance
“…Other studies have reached the same conclusions but also with critical limitations; however, it is important to note that PGRN has been included in a panel of urinary diagnostic markers for non-invasive detection of primary and recurrent urothelial urinary bladder carcinoma. So far, the analyses that have been performed are inconclusive and it is necessary to carry out larger or multicenter studies to substantiate the benefits of including PGRN in a diagnostic panel [86]. …”
Section: Progranulin As Cancer Biomarkermentioning
confidence: 99%
“…Other studies have reached the same conclusions but also with critical limitations; however, it is important to note that PGRN has been included in a panel of urinary diagnostic markers for non-invasive detection of primary and recurrent urothelial urinary bladder carcinoma. So far, the analyses that have been performed are inconclusive and it is necessary to carry out larger or multicenter studies to substantiate the benefits of including PGRN in a diagnostic panel [86]. …”
Section: Progranulin As Cancer Biomarkermentioning
confidence: 99%
“…The aim of the present study was to validate urinary midkine protein, suggested as a convenient biomarker for the non-invasive detection of BCa (17,18), in an independent patient cohort and to compare its diagnostic utility with that of VUC.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, midkine protein was demonstrated to be highly expressed in various malignancies, including neuroblastoma, breast cancer, hepatocellular carcinoma, colorectal cancer and BCa (15,16). Although the expression of midkine protein in BCa and its correlation with a poor outcome in patients with invasive cancers has been previously reported (16), to the best of our knowledge there are only three studies reporting the measurement of midkine protein in urine specimens from BCa patients (15,17,18). Only one study investigated whether there is a correlation between midkine protein concentration in urine and disease progression in terms of tumor stage and grade (17).…”
Section: Introductionmentioning
confidence: 99%
“…Yoshiki's group (Kageyama, et al 2009) also reported that CALR was highly expressed in urine samples from bladder urothelial carcinoma patients compared to urological patients without urothelial carcinoma and non-urological patients, and suggested that urinary CALR concentration may be a useful biomarker for bladder urothelial carcinoma with a sensitivity of 67.9% and specificity of 80.0%. In another study, urinary CALR was indicated as a potential biomarker for urothelial urinary bladder carcinoma (Soukup, et al 2015). In the human bladder cancer J82 cell line, CALR silencing reduced cell viability, cell cycle progression, adhesion, migration, PXN (Paxillin)/FAK axis activation, FUT1 expression and in vivo tumor growth and metastasis (Lu, et al 2014b;Lu, et al 2011).…”
Section: Bladder Cancermentioning
confidence: 99%